Пазарна ориентација, маркетинг стратегија и план – основни бизнис чекори за успешно конкурентско позиционирање на малите и средни претпријатија на пазарот – со посебен осврт на индустријата и пазарот на кондиторски производи во Р. Македонија - Јованов Марјанова, Тамара (Економски факултет, УКИМ, Скопје, 2013)
The doctoral thesis has been developed based on two key objectives: 1. Establishing and proving the great impact of small and medium enterprises (SMEs) on economic growth on national and global level and 2. Proving the positive effect of the application of modern marketing concept on the competitiveness of SMEs. The importance of SMEs has been analyzed and described based on key economic indicators, describing and determining the main characteristics and factors affecting their success/failure and measures of state support to SMEs in the Republic of Macedonia and the European Union. The effects of the application of modern marketing concept were described and analyzed in three areas - market orientation, marketing strategy and marketing planning. Data were obtained from primary and secondary sources, and the analysis was conducted using the software IBM SPSS19. The study provided the following results: 1. The importance of SMEs to the national economy is great, still, significant deficiencies in the state support measures were detected; 2. Market orientation of domestic enterprises, especially micro and small is at a low level, and on the other hand, the degree of market orientation has a direct positive impact on profitability and the size of the market share; 3. There are significant deficiencies in the current marketing activities of domestic enterprises, especially micro and small; 4. The formal marketing plan that results in continuous preparation of a written marketing plan is directly related to and affects the profitability of the enterprise. The results of this research are useful for the existing domestic companies as a guide towardimproving their current practices in the field of marketing, as well as for potential domestic and foreign entrepreneurs who want to enter this arena.
Market orientation, marketing strategy and plan – basic business steps for successful competitive positioning of the SMES on the market – with a special focus on the confectionary industry and market in Republic of Macedonia
Докторска дисертација одбранета во 2013 година на Економскиот факултет во Скопје, под менторство на проф. д–р Митре Стојановски.
Keywords: SMEs, entrepreneurship, market orientation, marketing strategy, marketing plan